Independent and Interactive Associations of Fitness and Fatness With Changes in Cardiometabolic Risk in Children: A Longitudinal Analysis - Shang, Xianwen; Li, Yanping; Xu, Haiquan; Zhang, Qian; Hu, Xiaoqi; Liu, Ailing; Du, Songming; Li, Tingyu; Guo, Hongwei; Li, Ying; Xu, Guifa; Liu, Weijia; et al. (Frontiers in Endocrinology, 2020)
Background Findings for associations between cardiorespiratory fitness (CRF) and cardiometabolic risk (CMR) factors are inconsistent and the interactive association between CRF and fatness with CMR factors is unclear in children. Our study aimed to examine whether CRF and fatness are independently and interactively associated with CMR factors. Methods We included 5869 children aged 6-13 years in the analysis. Physical examinations, blood tests, and CRF were measured at baseline and one year later. CMR score (CMRS) was computed by summing Z scores of waist circumference (WC), averaged systolic and diastolic blood pressure (SBP and DBP), glucose, high-density lipoprotein cholesterol (HDL-C, multiplied by -1), and triglycerides. Results There was a high correlation between fatness and CRF in both boys and girls. High baseline CRF was independently associated with favorable changes in CMRS, BMI, WC, percent body fat (PBF), total cholesterol, LDL-C and HDL-C (all P-values<0.025). Improved CRF was independently associated with favorable changes in CMRS, BMI, WC, PBF, total cholesterol, LDL-C, HDL-C, triglycerides, and fasting glucose (all P-values<0.0321). Baseline BMI was positively associated with changes in CMRS, WC, blood pressure, triglycerides, insulin, and HOMA-IR (all P-values<0.0462). Low PBF at baseline was associated with favorable changes in CMRS, BMI, WC, blood pressure, HDL-C, triglycerides, insulin, and HOMA-IR (all P-values<0.0423). The percentage of the total effect of baseline CRF on changes in CMRS, triglycerides, HDL-C, PBF and WC mediated by baseline BMI was 66.0%, 61.6%, 40.3%, 20.7%, and 9.2%, respectively. Baseline CRF was a significant mediator for the association between baseline BMI and changes in CMRS (mediated by 4.3%), triglycerides (5.1%) and HDL-C (12.0%). An inverse association between baseline CRF and CMRS in children with high baseline BMI/PBF only. Improved CRF was associated with decreased BMI and WC in children with low baseline CRF. Conclusions Fatness and CRF are each independently associated with changes in CMR factors. Fatness is a major mediator for the association between CRF and CMR factors whilst the association between fatness and CMR factors is also mediated by CRF. The beneficial effect of high CRF on CMR factors was more evident in obese or unfit children.